A Bibliometric Analysis on Relationship of Corporate Social Responsibility and Financial Reporting Using Scopus Database - Pavithra, J.; Verma, Ashutosh; Harini, B.; Arasuraja, G.; Vinothini, A.; Nazrine, N A (Indian Journal of Information Sources and Services, 2025)
Crucially important for corporate governance, CSR (Corporate Social Responsibility) influences how businesses match their operations with moral, environmental, and social values. This study examines how CSR programs affect financial reporting, emphasizing how stakeholder trust, transparent disclosure, and organizational performance are intertwined. CSR into financial reporting standards. To better connect financial disclosures with Environmental, Social, and Governance (ESG) measures, this paper examines how CSR reporting improves transparency and fortifies brand reputation. It also looks into the regulatory environment, including the function of required and optional disclosure standards and how they affect the reliability of financial statements. The bibliometric analysis will allow us to identify research studies that are carried out on the effect of financial position on corporate performance. The database is collected from Scopus and other renowned sources. The research analyzes companies that can impact their profitability through CSR activities.